Implementation Of The Problem Based Learning Model To Improve Students' Creative Thinking Ability (IPF: Inovasi Pendidikan Fisika, 2022)
Abstract The purpose of this study is to analyze the increase in students' creative thinking skills based on article reviews with the implementation of the Problem Based Learning learning model. This research includes qualitative research with the type of research using library research, namely library research that uses data grouping methods and then carried out by analyzing and reviewing various relevant journals and research articles. By using analysis techniques of collection, unification and identification of secondary data obtained from several relevant studies. Based on the results of this study, it can be obtained that the application of the Problem Based Learning learning model itself can improve students' creative thinking skills. In the research that has been done through library research, it was found that the students' creative thinking ability showed increasing results, including in the medium category. In this study, the increase in students' creative thinking skills was also seen from four aspects, namely fluency, flexibility, originality, and elaboration. This is obtained from the results of the pre-test and post-test. So it can be concluded that the implementation of the learning model that Problem Based Learning can improve students' creative thinking skills. This is obtained from the results of the pre-test and post-test. So it can be concluded that the implementation of the learning model that Problem Based Learning can improve students' creative thinking skills. This is obtained from the results of the pre-test and post-test. So it can be concluded that the implementation of the learning model that Problem Based Learning can improve students' creative thinking skills. Keywords:Problem Based Learning, Creative Thinking, Literature study